Godsdienstige perspektiewe in die heropbou van die gemeenskap - Crafford, D. (Verbum et ecclesia, 1995)
Religious perspectives in the reconstruction of the society The multi-religious context in South Africa is a fact and must be taken into account in any effort towards reconstruction and development of the society. The different religiOns are challenged to participate in the process of reconstruction. In many ways they can contribute positively towards the process. There are however also elements in religions which can hinder and obstruct the process. 17lis article considers a number of perspectives in Islam, Hinduism, African Traditional Religion and Christianity which can have a positive or negative influence on the Reconstruction and Development Program in South Africa.